2021
DOI: 10.1007/s11523-021-00820-7
|View full text |Cite
|
Sign up to set email alerts
|

Starting Imatinib at 400 mg Daily in Patients with Gastrointestinal Stromal Tumors Harboring KIT Exon 9 Mutations: A Retrospective, Multicenter Study

Abstract: Background Retrospective analyses suggest that patients with advanced KIT exon 9-mutated gastrointestinal stromal tumors (GISTs) receiving imatinib 800 mg (rather than 400 mg) daily have better outcomes. In the adjuvant setting, the question of the optimal dose of imatinib remains unsettled. Objective We aimed to retrospectively assess the activity of imatinib 400 mg in both the adjuvant and the advanced settings. Patients and methods We performed a multicenter study of patients with KIT exon 9-mutated GIST st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Moreover, considering the relatively poor outcomes of the few patients with KIT exon 9–mutated GIST enrolled in available randomized clinical trials ( 11, 12, 24 ), the role of adjuvant imatinib in KIT exon 9–mutated GIST remains to be clearly defined. In a small series, a benefit from imatinib 400 mg per day in high-risk patients with exon 9–mutated GIST compared with no treatment was recently reported ( 33 ). At the current stage, it should be however highlighted that our retrospective real-world evidence is not sufficiently strong to recommend any change to current therapeutic standards and policies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, considering the relatively poor outcomes of the few patients with KIT exon 9–mutated GIST enrolled in available randomized clinical trials ( 11, 12, 24 ), the role of adjuvant imatinib in KIT exon 9–mutated GIST remains to be clearly defined. In a small series, a benefit from imatinib 400 mg per day in high-risk patients with exon 9–mutated GIST compared with no treatment was recently reported ( 33 ). At the current stage, it should be however highlighted that our retrospective real-world evidence is not sufficiently strong to recommend any change to current therapeutic standards and policies.…”
Section: Discussionmentioning
confidence: 99%
“…These data raise the question of whether imatinib at a dose of 400 mg/day represents an adequate standard for Ex9-GIST patients. A recent retrospective analysis on a small sample size suggested that imatinib at 400 mg/day in high-risk Ex9-GIST patients might be beneficial compared to no treatment [65]. Given the data supporting the use of 800 mg/day in patients with advanced Ex9-GISTs (see next paragraph), some expert clinicians, where local policies allow it, prefer to offer this dose in the adjuvant setting also.…”
Section: Ex9-gist In the Adjuvant Settingmentioning
confidence: 99%
“…Based on these data, imatinib at a dose of 800 mg/day is considered a standard treatment in Ex9-GIST patients, where local and national policies allow it. Intrapatient dose escalation, i.e., starting treatment at 400 mg/ day and offering 800 mg/day upon progression, also appears to be a feasible strategy [65]. Importantly, high-dose imatinib has been associated with a higher risk of toxicities, and continuation of the treatment is highly dependent on patients' compliance and supportive measures [76].…”
Section: Ex9-gist In the Metastatic Settingmentioning
confidence: 99%
“…[8][9][10] Previous studies have shown that imatinib is less effective in GIST patients with KIT exon 9 mutations, and their progression-free survival (PFS) and overall survival (OS) rates are short. 11,12 Therefore, early determination of the KIT exon 9 mutation in patients with GIST is important for accurate prognosis and timely treatment. At present, the determination of KIT-related genes mainly depends on surgery or biopsy to obtain tissue samples, which is invasive and expensive.…”
Section: Introductionmentioning
confidence: 99%